Derivation of Z-γ (Reflectivity-specific attenuation) relation for satellite link in tropical region - Badron, Khairayu; Ismail, Ahmad Fadzil; Ismail, Maszlan; Salim, Hamid; Mustapha, Hafizah (American Scientific Publishers, 2016)
The investigation of deriving the Z-γ (reflectivity-specific attenuation) relation is critical in the development of a novel rain attenuation prediction for a satellite link using radar information. Comparison between S-band radar derived reflectivity data and measured received power signals of X-band RazakSAT’s Malaysian remote satellite link is presented. RazakSAT’s satellite link received power during clear sky and rainy conditions are compared to extract the rain attenuation values. The specific attenuation of the link can be derived from the rain attenuation values. The S-band radar with horizontal polarization reflectivity information was used to compare the likely rain attenuation along the same RazakSAT satellite propagation paths. Both reflectivity information and specific attenuation data are tabulated during the RazakSAT operation in 2009 to derive the relationship. Later, the radar reflectivity values, Z are converted into specific attenuation, γ using the derived relationship of the Z-γ to calculate the rain attenuation and fade margin for a slant path link. The current rain attenuation prediction is using point rainfall but in this technique the reflectivity values is being explored. The relationship is derived using similar path length, elevation angle, time and date from the RazakSAT link and the radar information for both stratiform and convective events. Therefore, the relationship can be a good landmark for the future engineers and researchers to estimate the rain attenuation using radar information.